An improved novel Hill cipher using RCLT Title of the article - Hema, V; M. Ganaga Durga, Dr (International Journal of Engineering and Technology, 2018)
Security is the only buoyant to the frailest link. In this communication world, the implementation of sturdy cryptographic and integrity checking algorithms is the smart solution to the frailest link. So, the proposed paper provides the new-fangled pattern of cryptographic scheme in concert with Number Theory which safeguard the integrity and confidentiality of intricate data and communications. By using this system, clientâ€™s burden of security issues associated with the data hosting in the untrusted remote server is abridged. By manipulating some features of the Galois Field, a new method of key generation is proposed. The proposed system is resilient against the various attacks and cannot be understood by the intruders. It is simple yet robust and will surely improve the overall security with higher efficiency.Â